Structural and Functional Abnormalities in Knee Osteoarthritis Pain Revealed With Multimodal Magnetic Resonance Imaging - Guo, Hua; Wang, Yuqing; Qiu, Lihua; Huang, Xiaoqi; He, Chengqi; Zhang, Junran; Gong, Qiyong (Frontiers in Human Neuroscience, 2021)
The knee osteoarthritis (KOA) pain is the most common form of arthritis pain affecting millions of people worldwide. Long-term KOA pain causes motor impairment and affects affective and cognitive functions. However, little is known about the structural and functional abnormalities induced by long-term KOA pain. In this study, high-resolution structural magnetic resonance imaging (sMRI) and resting-state functional MRI (rs-fMRI) data were acquired in KOA patients and age, sex-matched healthy controls (HC). Gray matter volume (GMV) and fractional amplitude of low-frequency fluctuation (fALFF) were used to study the structural and functional abnormalities in patients with KOA. Compared with HC, KOA patients showed reduced GMV in bilateral insula and bilateral hippocampus and reduced fALFF in left cerebellum, precentral gyrus, and the right superior occipital gyrus. KOA patients also showed increased fALFF in left insula and bilateral hippocampus. In addition, the abnormal GMV in left insula, fALFF in left fusiform were closely correlated with pain severity or disease duration. These results indicated that long KOA pain leads to brain structural and functional impairments in motor, visual, cognitive, and affective functions related brain areas. Our finding may facilitate understanding of neural basis of KOA pain and the future therapy to relieve disease symptoms.